Surface Dependent Dual Recognition of a G-quadruplex DNA With Neomycin-Intercalator Conjugates - Ranjan, Nihar; Andreasen, Katrine F.; Arora, Yashaswina; Xue, Liang; Arya, Dev P. (Frontiers in Chemistry, 2020)
G-quadruplexes have been characterized as structures of vital importance in the cellular functioning of several life forms. They have subsequently been established to serve as a therapeutic target of several diseases including cancer, HIV, tuberculosis and malaria. In this paper, we report the binding of aminosugar-intercalator conjugates with a well studied anti-parallel G-quadruplex derived from Oxytricha Nova G-quadruplex DNA. Of the four neomycin-intercalator conjugates studied with varying surface areas, BQQ-neomycin conjugate displayed the best binding to this DNA G-quadruplex structure with an association constant of Ka = (1.01 ¬±0.03) × 107 M-1 which is nearly 100 fold higher than the binding of neomycin to this quadruplex. The binding of BQQ-neomycin displays a binding stoichiometry of 1:1 indicating the presence of a single and unique binding site for this G-quadruplex. In contrast, the BQQ-neomycin displays very weak binding to the bacterial A-site rRNA sequence showing that BQQ-does not enhance the neomycin binding to its natural target, the bacterial rRNA A-site. The BQQ-neomycin conjugate is prone to aggregation even at low micromolar concentrations (4 μM) leading to some ambiguities in the analysis of thermal denaturation profiles. Circular dichroism experiments showed that binding of BQQ-neomycin conjugate causes some structural changes in the quadruplex while still maintaining the overall anti-parallel structure. Finally, the molecular docking experiments suggest that molecular surface plays an important role in the recognition of a second site on the G-quadruplex. Overall, these results show that molecules with more than one binding moieties can be made to specifically recognize G-quadruplexes with high affinities. The dual binding molecules comprise of quadruplex groove binding and intercalator units, and the molecular surface of the intercalator plays an important part in enhancing binding interaction to the G-quadruplex structure.